Pembeli Bona Fide Dalam Penipuan Tanah:Isu Dan Cabaran (UUM Journal of Legal Studies, 2015)
The legal position applicable in Malaysia based on the decision of Adorna Properties Sdn Bhd v Boonsom Boonyanit [2001] 2 CLJ 133 is that the right of the original owners of a land title is not fully protected if the property was transferred to another party by means of fraud, provided the new owner (buyer) has acquired ownership with bona fide (good faith) with consideration. The original owner is not legally entitled to recover the land from the new buyer. In other words, with this decision even though the conversion of ownership was obtained by fraud, if the registered buyer is a bona fide purchaser, the ownership is undeniable. The decision of this case became a binding precedent to all courts in Malaysia and the principle in this case can only be restored or corrected by another decision of the Federal Court. In 2010, the case of Tan Yin Hong v Tan Sian San [2010] 2 CLJ 269 which was decided by the Federal Court was a landmark case which revised the legal principles applied in Adorna Properties.The legal position after the decision of the case in 2010 clearly shows that the original owner has undeniable ownership and has the right to reposses the land when fraud is proven. This purpose of the article is to study the position and the remedy of the bona fide purchaser when the decision in favor of the landowner which may invite injustice to the bona fide purchaser as they solely depending on the document title when dealing with transfer of land matters.The methodology used in this study is a library based research which includes document analysis such as the decided cased, books and articles. This study also raises suggestions of improvement and outcome to ensure the interests and rights of the parties involved. Keywords: bona fide purchaser, ranking and remedies, challenges, suggestions for improvement.